2008
DOI: 10.1016/j.micres.2006.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and vertical transmission of Streptococcus mutans in Turkish children

Abstract: The aim of the study was to establish the colonization of Streptococcus mutans and to determine the possibility of intra-familial transmission in a group of Turkish children and their parents. A total of 56 children participated in the study together with their parents (20 fathers and 49 mothers). Saliva samples were collected from the individuals and cultivated on S. mutans selective TYCSB agar. The typical isolates of S. mutans were identified by using classical microbiological methods, as well as molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 13 publications
1
28
1
7
Order By: Relevance
“…Others have reported transmission between family members, such as spouse-spouse, father-child, and sibling-sibling (Saarela et al, 1993;Li and Caufield, 1998;Redmo Emanuelsson and Wang, 1998;Kozai et al, 1999;Emanuelsson and Thornqvist, 2000;van Loveren et al, 2000;Redmo Emanuelsson and Thornqvist, 2001;Nie et al, 2002;Tedjosasongko and Kozai, 2002;Ersin et al, 2004;Hames-Kocabas et al, 2008). Although there have been three reports of transmission between unrelated young infants in nursery schools in China, Brazil, and Japan (Mattos-Graner et al, 2001;Tedjosasongko and Kozai, 2002;Liu et al, 2007), these children ranged in age from 2 mos to 4 yrs, when salivary transfer is more likely than in older children.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported transmission between family members, such as spouse-spouse, father-child, and sibling-sibling (Saarela et al, 1993;Li and Caufield, 1998;Redmo Emanuelsson and Wang, 1998;Kozai et al, 1999;Emanuelsson and Thornqvist, 2000;van Loveren et al, 2000;Redmo Emanuelsson and Thornqvist, 2001;Nie et al, 2002;Tedjosasongko and Kozai, 2002;Ersin et al, 2004;Hames-Kocabas et al, 2008). Although there have been three reports of transmission between unrelated young infants in nursery schools in China, Brazil, and Japan (Mattos-Graner et al, 2001;Tedjosasongko and Kozai, 2002;Liu et al, 2007), these children ranged in age from 2 mos to 4 yrs, when salivary transfer is more likely than in older children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mutans streptococci is transmitted between mother and child primarily by vertical transmission and thus is a major risk factor in early and future caries ECC with similar bacterial genotypes being common within a family [20]. Whether the familial associations are due to exposures in a shared environment, parental culture, awareness (health literacy), familial (genetic) factors or whether this liability is related to the disorder itself remains to be determined.…”
Section: Genetic and Familial Predispositionmentioning
confidence: 99%
“…Genotyping was undertaken by arbitrarily primed-PCR (AP-PCR) [26] using primer OPA5 (5′-AGGGGTCTTG-3′) [27]. Each reaction mixture (total volume = 50 μl) contained 5 μl of 10 × Taq buffer, 300 of µM dNTPs, 2 μM of primer, 5 μl of template, and 5 U of Taq DNA polymerase.…”
Section: Genotyping Of Clinical Isolates Of S Mutans By Arbitrarily mentioning
confidence: 99%